Investigation for the presence of bacteria and antimicrobial resistance genes in sea snails (Rapana venosa) - Ozbey, Gokben; Tanriverdi, Elif Seren; Basusta, Asiye; Lakshmanappa, Yashvanth Shaan; Otlu, Baris; Zigo, Frantisek (Inst Rural Health Lublin, Poland, 2023)
Introduction and Objective. The aims of this study were to search for the presence of bacteria in sea snails (Rapana venosa) by using culturomics and Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), and the antibiotic resistance/susceptibility of the sea snails.Materials and method. The anti-microbial susceptibilities of Gram-negative bacteriawas assessed by the Kirby-Bauer disk diffusion method, the presence of the mcr genes (mcr-1 to-5), the major carbapenemase and 13-lactamase resistant genes in Gram-negative bacteria, using mPCR method and 16S rRNA sequence analysis of A. hydrophila isolates.Results. Bacterial growth accounted for 100% and 94.2% in the samples of intestine and meat, respectively, in the snails. The main organisms identified by MALDI-TOF MS were A. salmonicida subsp. salmonicida at 33.7%, followed by Raoultella ornithinolytica at 9.6% (10/104) and Staphylococcus warneri at 7.7% in meat and intestine samples. Aeromonas hydrophila/ punctata (caviae), Aeromonas sobria, Klebsiella aerogenes, Klebsiella oxytoca, Raoultella planticola, Shewanella putrefaciens and Vibrio vulnificus are intrinsic or chromosomally-mediated resistant against ampicillin. No mcr genes (mcr-1 to-5), the major carbapenemase and 13-lactamase resistant genes were found. Aeromonas salmonicida subsp. salmonicida showed very low levofloxacin and meropenem resistance levels at 2.9%. When the sequence was searched in the Blast database, the genome of A. hydrophila/punctata (caviae) isolate showed high similarity with the A. hydrophila sequences. Conclusions. The findings obtained not only provide data about the proportion of bacteria in the gut and meat of the sea snails and their antibiotic resistance/susceptibility, but also show the absence of carbapenemase, colistin, and 13-lactamase resistant genes among bacterial isolates from sea snail gut microbes.
Keywords: Carbapenem; colistin; MALDI-TOF MS; resistance genes; sea snail